Regulation and characterization of the nitrogen assimilatory gene cluster in Clostridium acetobutylicum P262 - Stutz, Helen (Department of Molecular and Cell Biology, 2023)
The solventogenic Clostridium acetobutylicum strain P262 was used for the commercial production of solvents in South Africa from 1945 to 1983 (Jones and Woods, 1986a). Our laboratory has focused on understanding two: fundamental aspects of its physiology, namely nitrogen metabolism and electron transport pathways. The long-term goal is the potential genetic modification of nitrogen utilization and/or electron distribution in the cell, to manipulate fermentation patterns for improved growth rate and solvent yields. The main aims of this research project were to: extend the sequence analysis of the glnA locus encoding the glutamine synthetase (GS) enzyme (Janssen et al., 1990; Fierro-Monti et al., 1992); to identify and characterize the locus encoding the structural genes for the glutamate synthase (GOGAT) enzyme; and to detennine the mechanisms and growth conditions which regulate the activity of these two key enzymes of nitrogen assimilation. In addition, we were interested in characterizing clone pMET13Cl, which was isolated by a selection system developed to clone genes involved in electron transport from C. acetobutylicum (Santangelo et al., 1991). Sequence analyses revealed that the region downstream of glnA and the putative regulatory gene, glnR (Reid and Woods, 1995), encoded the structural genes for the large (a) and small (J) subunits of GOGAT, respectively. This is the first report in which the genes encoding GS and GOGAT are genetically linked. The a subunit was designated gltA, and the downstream f3 subllll.it was designated gltB. All the likely cofactor and substrate binding sites identified in GOGAT enzymes (Vanoni and Curti, 1999) were conserved in the deduced gltA and gltB polypeptides. The identity of the gltA and gltB genes were functionally confirmed by complementation studies involving their co-expression from separate constructs in an E. coli glutamate auxotroph (strain: Mx:3004), which restored the ability of this mutant to grow with ammonia as the sole source of nitrogen. Physiological studies on the germination, growth and differentiation patterns of C. acetobutylicum P262 were assessed in relation to different nitrogen conditions. Significantly, organic nitrogen (casamino acids) was the preferred source of nitrogen, and not ammonia as ll previously asswned. These studies led to the development of nitrogen limiting conditions (0.025% casamino acids + 0.15% glutamine) and nitrogen rich conditions (0.2% casamino acids) used for regulatory studies. GOG AT activity was optimised. It appeared to be sensitive to oxygen and specific for the co-enzyme NADH. Both GS and GOGAT activities were regulated by the nitrogen source in a similar way: induced in the nitrogen limiting conditions and repressed in the nitrogen rich conditions. Northern blot analyses, in conjunction with the enzyme activity profiles and feedback inhibition studies, indicated that GS and GOGAT activities were regulated primarily at the level of transcription. Furthermore, glnA. andglnR, and gltA and gltB are each transcribed as an operon under nitrogen limiting conditions. No assimilatory GDH activity could be detected. The implications of these results, as well as sequence features identified, are discussed in context with a proposed model for the regulation of GS and GOGAT activity in C. acetobutylicum P262. Analysis of plasmid pMET13Cl identified a gene whose predicted -46 kDa product was associated with an electron transport function. The deduced amino acid sequence was not typical of electron transport proteins, but rather shared striking homology to bacterial GOGAT p subunit polypeptides. This p subunit-like gene was thus designated gltX. We were, however, unable to relate it to GOGAT activity or nitrogen metabolism. Rather, it appears to belong to a novel family of FAD-dependent NAD(P)H oxidoreductases suggested by Vanoni and Curti (1999) and supported by an analysis of the evolutionary relationships of the GOGAT subunits/domains from various sources.